Molecular docking analysis of six major compounds from sweet basil (Ocimum basilicum L.) extract as potential anti-hypertension therapy - Bayu Cakra Buana; Iksen Iksen; Kasta Gurning (Pascasarjana Universitas Negeri Medan, 2023)
Hypertension is an abnormally high blood pressure condition that is the leading cause of preventable cardiovascular disease, chronic kidney disease, and cognitive impairment. In the case of hypertension, repressing the Angiotensin-Converting Enzyme (ACE) expression has been shown to be an effective method of controlling hypertension by inhibiting the conversion of angiotensin I to angiotensin II. Captopril is the most commonly used ACE inhibitor. It simultaneously inhibits the conversion of angiotensin I to the potent vasoconstrictor angiotensin II and the vasodilator peptide bradykinin. Sweet basil (Ocimum basilicum L.) on the other hand, is used in traditional Indian and Chinese medicine to treat a variety of diseases, including hypertension. The study aimed attempts to investigate the potency of 6 major compounds found in sweet basil (Ocimum basilicum L.) extract, as an anti-hypertension therapy. The analysis demonstrates that Ocimum basilicum L., extract is effective as an anti-hypertension therapy because it contains several compounds that may interact with ACE and inhibit its activity. The molecular docking analysis and drug-likeness prediction indicate that camphor could be a potential drug candidate because it does not violate the Lipinski rule, has a high Gastrointestinal (GI) absorption, a high affinity to interact with ACE, and a similar interaction site to the ACE-Captopril interaction.Keywords: ACE; Holly basil; Hypertension; Molecular docking